2011
DOI: 10.1080/14766086.2011.552255
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the Personal Ethical Threshold and workplace spirituality

Abstract: This article explores the relationship between the Personal Ethical Threshold and workplace spirituality. We begin by reviewing our concept of the Personal Ethical Threshold, or PET, defined as an individual’s vulnerability to organizational pressures that can derail moral intentions. Next, we consider how individuals resolve their intrapersonal conflict when they violate their moral principles and we explain how to assess the PET. We tie the PET to workplace spirituality by focusing on flow as the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…This gets endorsed by the findings that WS is positively related to MC. MC is recognized as the connecting line between identifying what is morally right and the inner strength to act on it (Comer and Vega, 2011). On the other hand, WS provides the much-needed encouragement to employees to do the right thing at the workplace, ignoring any negative consequences (McGee and Grant, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gets endorsed by the findings that WS is positively related to MC. MC is recognized as the connecting line between identifying what is morally right and the inner strength to act on it (Comer and Vega, 2011). On the other hand, WS provides the much-needed encouragement to employees to do the right thing at the workplace, ignoring any negative consequences (McGee and Grant, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Johnson (2009) posited that WS can motivate leaders to put others over self and foster altruistic behavior through its emphasis on connection and community. Further, such leaders who follow moral principles and possess strong personal ethics are likely to be viewed as moral role models by their followers (Comer and Vega, 2011). Koburtay and Haloub (2020) argued that spiritually inclined organizations enhance the ethical and spiritual leadership behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, McGhee and Habets (2018) found that Christians helped set the ethical tone at work and contributed to sustainable ethical change. The literature supports this, affirming that the intrinsically religious (i.e., those for whom religion is more than affiliation) are more ethical in business (Kennedy and Lawton 1998;Singhapakdi et al 2000;Longnecker et al 2004;Emerson and McKinney 2010;Comer and Vega 2011), and take a stronger stance on corporate social responsibility (Angelidis and Ibrahim 2004;Jamali and Sdiani 2013;Mazereeuw-van der Duijn Schouten et al 2014). Such behavior contradicts the tendency in many organizations to suppress moral choices, to value means more than ends, and to ignore social and environmental costs (Moore 2008).…”
Section: What Does This Mean For Christian Saw?mentioning
confidence: 98%
“…Of course, individual differences need to be considered as well. Not only do people differ in terms of how important being a moral person is to them (Aquino and Reed 2002), but they also differ in terms of how susceptible they are to organizational pressures to do immoral things (Comer and Vega 2011), and such dispositional factors require further research attention. We have seen that the study of moral and ethical behavior can be split into the study of what one ought to do and how one actually does it.…”
Section: Morality In the Workplace: Possible Implicationsmentioning
confidence: 98%